Harvesting the uncollected fruits of other people’s intellectual labour - Timmermann, Cristian (Acta Bioethica, 2017)
Intellectual property regimes necessarily create artificial scarcity leading to wastage, both by blocking follow-up research and impeding access to those who are not able to pay the full retail price. After revising the traditional arguments to hinder access to people’s intellectual labour, we examine why we should be more open to allow free-riding of inventive efforts, especially in cases where innovators have not secured the widest access to the fruits of their research. We do so by questioning the voluntariness involved in the consumption of objects of innovation, restating the positive social externalities that arise when wider access to the fruits of innovation is facilitated, and examining the eventual harms innovators face.